Diversification in the mountains: a generic reappraisal of the Western Ghats endemic gecko genus Dravidogecko Smith, 1933 (Squamata: Gekkonidae) with descriptions of six new species - Chaitanya, R.; Giri, Varad B.; Deepak, V.; Datta-Roy, Aniruddha; Murthy, B.h.c.k; Karanth, Praveen (Zootaxa, 2019)
The monotypic genus Dravidogecko, represented by its type-species D. anamallensis, is singular amongst peninsular Indian gekkonid lineages in its endemism to the Western Ghats. Molecular species delimitation approaches reveal at least seven species-level lineages within the genus from its distribution range across the mid–high elevations of the southern Western Ghats of India. These lineages, albeit superficially cryptic, are patently diagnosable from each other by employing a limited but precise set of morphological characters. Six of these lineages that were obscured under the nomen D. anamallensis are herein recognized as distinct species. A reappraisal of the genus Dravidogecko is provided based on external morphology and osteological characters, along with a detailed redescription of the holotype of D. anamallensis. A key to the species based on diagnostic characters is presented. Gene-trees based on mitochondrial and nuclear DNA data recovered marginally disparate topologies and were consequently coalesced into a species-tree for phylogenetic inference. Timetree analysis reveals late Miocene cladogenesis in this group and establishes late Palaeocene divergence from its sister genus, Hemidactylus, making Dravidogecko one of the earliest, extant lizard lineages to have colonized peninsular India.